(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
In this study, zeolite was used as a catalyst in a catalytic cracking reaction of waste cooking oil, which generates compositions similar to gasoline. This reaction was catalyzed by batch distillation of WCO in a hydrothermal reactor with zeolite catalyst synthesized using local clay sediment. The catalytic cracking was carried out under ambient conditions using 100-ml distillation apparatuses placed on a heating mantle and 50g of oil-added variable catalyst loading from 2 to 10 Wt% with zeolite as catalyst. The heating rate, residence time, and catalyst loading influenced the product yield. The physicochemical properties of the product, such as the density, the flash point, and the kinematic volumetric viscosity, were examined for fuel suitability. Chemical gas chromatography-mass spectrometry (GC-MS) determined the chemical composition of the compounds present in the cracked product. The overall study showed that the product’s optimum zeolite loading, cracking temperature, and cracking rate were 8 wt%, 380 oC, and 0.0048 min-1, respectively. The study on zeolite catalytic cracking revealed that local clay synthesizes the zeolite catalyser, which is effective in WCO catalytic cracking for liquid fuel formation.